2000
DOI: 10.1210/jcem.85.11.7000
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antineutrophil Cytoplasmic Antibody Positivity in Childhood Onset Graves’ Disease Treated with Propylthiouracil

Abstract: Propylthiouracil (PTU)-induced antineutrophil cytoplasmic antibody (ANCA)-related vasculitis and nephritis were recently reported in about 30 patients with hyperthyroidism. The objective of this study was to clarify the prevalence of ANCA and the relationship between ANCA and thyroid antibodies in children with Graves' disease. Titers of myeloperoxidase (MPO)-ANCA in sera of 51 patients with childhood onset Graves' disease (16 before treatment, 25 and 10 treated with PTU and methimazole, respectively) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 24 publications
3
19
1
Order By: Relevance
“…A high frequency of ANCA positivity has been reported in patients receiving treatment with antithyroid medication [22,27,29]. Both antithyroid drugs may lead to asymptomatic ANCA positivity, but PTU is the agent which causes most frequent ANCA positivity [22,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…A high frequency of ANCA positivity has been reported in patients receiving treatment with antithyroid medication [22,27,29]. Both antithyroid drugs may lead to asymptomatic ANCA positivity, but PTU is the agent which causes most frequent ANCA positivity [22,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al 19 and Wada et al 21 reported that none of the MPO-ANCA-positive Graves'-disease patients developed ANCA-associated disorders. An intriguing hypothesis is that MPO-ANCA may be pathogenic only in patients with a synergistic inflammatory event, such as an infection that induces priming of PMN, or with a certain immunological background which may determine disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentage of MPO-ANCA-positive patients did not correlate with the duration of PTU treatment in patients in this study. Sato et al 19 showed that 16 (64%) of 25 childhood-onset Graves'-disease patients receiving PTU were MPO-ANCA-positive. Gunton et al 20 and Wada et al 21 also described a significant incidence of MPO-ANCApositive sera in patients treated with PTU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no such link has been found in adult patients with AASV [21]. Environmental factors, such as propylthiouracil in MPA, may act as a disease trigger in susceptible children [22,23]. Infection, particularly with Staphylococcus aureus, has also been linked to WG, with nasal carriage in WG patients being associated with disease relapse [24] and clearance with cotrimoxazole reducing the risk of relapse [25].…”
Section: Anca-associated Systemic Vasculitismentioning
confidence: 99%